UJI AKTIVITAS GETAH GAMBIR(Uncariagambir Roxb.) TERHADAP BAKTERI Escherichia coli DAN Salmonella typhi - Adiansyah Adiansyah; Ahmad Gazali Sofwan; Siti Nurbaya; Lestari Simanjuntak (Jurnal Farmanesia, 2017)
Gambir is an extract of the leaf sap and twigs of the Gambir plant (Uncariagambir Roxb.) which has been dried. According to information, Gambir sap can be used as a mixture of drugs for burns, headache medicine, diarrhea medicine, mouthwash, thrush medicine. Because there is the main content of catechins and tannins. The purpose of this study was to determine the antibacterial activity of secondary metabolites and the concentration of Gambir sap (Uncariagambir Roxb.) against Escherichia coli and Salmonella typhi bacteria. The method used is agar diffusion using disc paper. The results showed that the diameter of the inhibition of Gambir sap on Escherichia coli bacteria at a concentration of 300 mg/ml in the bacterial test was 16.03 mm, at a concentration of 200 mg/ml there was a bacterial test of 15.00 mm and Salmonella typhi at a concentration of 300 mg/ml contained bacterial test 16.06 mm, at a concentration of 200 mg/ml bacterial test 16.03 mm.